KRITERIA WALIMATUL ‘URSY YANG WAJIB DAN TIDAK WAJIB DIDATANGI PERSPEKTIF HUKUM ISLAM - Siti Maesaroh; Soiman Soiman (Fakultas Syariah, Prodi Ahwal As Syakhsiyah (AS) Universitas Nahdlatul Ulama Al-Ghazali (UNUGHA) Cilacap, 2022)
People's lives in general, most of them when attending walimah events do not pay attention to the ethics or criteria contained in the walimah. So that they will freely come to attend the walimah to fulfill the invitation they have received from the inviter. They are also more likely to not care about what it will be like and how the implementation of the walimah they will attend will be like. This research is research that uses library research (library) research methods. Meanwhile, the approach used is a qualitative research approach. Based on the opinion of the Syafi'i Madzhab, the criteria for walimatul 'ursy that must be met are that the implementation of the walimah does not deviate from the applicable rules of Islamic law, such as the absence of evil, for example the provision of wine and singers (hired singers) which if carried out will result in riots or quarrels, something which makes people complacent. Meanwhile, the criteria that are not required to be met include the existence of wrongdoing in the implementation of walimatul 'ursy. Meanwhile, the criteria for walimatul 'ursy in terms of customs or habits are al-'adah al-muhakkamah, which includes good and valid customs or habits (al-'adah as-shahihah.